A coincidence theory involving Fredholm operators of nonnegative index - Gabor, Dorota; Kryszewski, Wojciech (Topological Methods in Nonlinear Analysis, 2000)
We construct a homotopy invariant appropriate for studying the existenceof coincidence points of Fredholm operators of nonnegative index and multivaluedadmissible maps. Cohomotopy methods are used as a more suitable tool than homological ones.Both finite and infinite dimensional cases are investigated.